Wild mushroom exposures in Kansas, 2013–2018. Issue 1 (30th November 2021) - Wagner, Sam; Thornton, Stephen; Oller, Lisa; Wilson, Michelle; Hudson, Michael
Abstract: Background: Mushrooms exposures are uncommon, difficult to characterize, and occasionally cause serious morbidity and mortality. We describe mushroom exposures reported to the Kansas Poison Control Center (KSPCC). Methods: We queried the KSPCC database for all mushroom exposures from 1 January 2013 to 31 December 2018. We abstracted age, sex, exposure date, reason, management site, laboratory values, medical outcome, GI symptoms, interventions, mycologist consultation, presence of mushroom picture, and identification of the mushroom. Results: We identified 441 cases. Typical cases were young children with exploratory ingestion in summer managed at home (279) with no clinical effect (257). Vomiting or diarrhea occurred in 135 cases. Treatments included either no intervention or PO liquids (304), IV fluids (76), anti-emetics (59), or N-acetylcysteine (5). AST was normal in 52 of 55 cases. CPK was high in 3 of 7 patients. Care included hospital admission (56) including ICU in nine. There were no deaths. Most frequently identified were Chlorophyllum (29) and Psilocybe sp. (13). Conclusions: Mushroom exposures reported to KPCC were most common in summer months and typically involved unintentional exposures in young children. Vomiting and diarrhea occurred in approximately one-third of cases. Morbidity was minimal. No deaths occurred. In most cases, the mushroom was never identified.